USE OF ICT IN DISTANCE LEARNING FOR STUDENTS WITH FUNCTIONAL LIMITATIONS (Journal of Information Technologies in Education (ITE), 2014)
The article outlines the main advantages of distance learning (e-learning) for students with functional limitations, describes the types of learning models according to the process of interaction of stakeholders, characterizes the types of ICT applicable to each mode of interaction.
Keywords: distance learning; information and communication technologies; synchronous and asynchronous methods of learning interaction; education of disabled children